The Relationship Between Hindu Religious Education Learning Outcomes and Students' Affective Aspects - Paramitha; I Wayan Mandra (International Journal of Multidisciplinary Sciences, 2023)
This study aims to determine the relationship between Hinduism learning outcomes and the affective aspects of students at UPT SMPN 1 Tellu Limpo'e, Sidrap. This study uses a quantitative research design with a correlational approach. The population in this study were seventh grade students at UPT SMPN 1 Tellu Limpo'e. The sample selected was 32 students taken with stratified random sampling technique. The instruments used were questionnaire sheets and Hinduism learning outcomes assessment. The data analysis used was Pearson correlation analysis. The results showed that there was a significant relationship between Hinduism learning outcomes and the affective aspects of students at UPT SMPN 1 Tellu Limpo'e (r = 0.832; p < 0.05). The results of this study indicate that the higher the learning outcomes of Hinduism, the higher the affective aspects of students. Therefore, it is expected that religious teachers can improve Hinduism learning outcomes by developing creative and innovative learning strategies so that students can improve their affective aspects.